Enhancing Voltage Stability and Power Quality in Hybrid MPPT Algorithm Based SPV-Wind Hybrid Microgrid System Tied Utility Grid Integrating Modified STATCOM (Contemporary Mathematics, 2025)
Voltage sags can lead to equipment malfunction, decreased performance, and operational disruptions. They are typically caused by short circuits, motor start-ups, or sudden load increases, affecting power system reliability. Voltage stability of the proposed system has been improved by implementing modified Static Synchronous Compensator (m-STATCOM) by reducing voltage sags resulting power quality of the proposed system has been enhanced during breakdowns in electrical systems. The Voltage-Source Inverter (VSI) technology of m-STATCOM allows for quick reaction. At the Point of Common Coupling (PCC), it stabilizes voltage to avoid equipment damage from voltage fluctuations. m-STATCOM boosts reactive power regulation, renewable energy stability, and fault ride-through for dependable grid performance. Hybrid Incremental Conductance and Ripple Correlation Control (INC-RCC) for MPPT in PV and wind farms tracks Maximum Power Point Tracking (MPPT) under diverse situations to reduce power losses and fluctuations resulting improve efficiency and reaction speed as compared to Penguin Search (PS) optimization. System stability and performance improve with the Solar Photovoltaic (SPV)-Wind farm and Sinusoidal Pulse Width Modulation (SPWM)-Voltage Source Inverter (VSI)-based m-STATCOM controller. This integrated solution assists in minimizing LLG failure voltage drops.1KW SPV and 2.5 kW wind farm hybrid system connected to 400 V, 50 Hz utility grid integrated to the SPWM-VSI based m-STATCOM controller has been designed using MATLAB/Simulink.
Keywords: solar photovoltaic (SPV) system; static synchronous compensator (STATCOM); sinusoidal pulse width modulation (SPWM); voltage source inverter (VSI); double line to ground fault (LLG)